Kadazandusun language politeness in IPG student lectures - Vurisiah Dadong; Musirin Mosin; Mohd Nor Azan Abdullah (Human Resource Management Academic Research Society (HRMARS), 2025)
Kadazandusun language politeness from Sudawil (poetry) traditional Kadazandusun poetry, dislike of honesty (Norjietta Taisin, 2014). Comply to the rules of communication and avoid impolite speech (Fraser & Nolen, 1981). This study examines the Kadazandusun language politeness of six lecturers and nine students in lectures. Before conducting the interview, the researcher made an appointment with the participants to determine the time to observe the lecturer conducting a lecture with the IPG students. Interviews were recorded in audio and entered into Nvivo 12 plus to be interpreted to obtain themes, categories and coding. The findings of the study show that lecturers and students think that politeness in Kadazandusun language helps in the usage of politeness in Kadazandusun language in lectures with a polite attitude, voice and intonation, polite and elegant choice of words and sentences, greetings, correct calls and appropriate language style. In this study, a sub-theme that contributes to the formation of lecture themes related to aspects of Kadazandusun politeness has been formed from the knowledge and experience of lecturers and students who consequentially use Kadazandusun politeness during lectures. A discussion about the use of politeness in Kadazandusun in lectures and suggestions to increase the potential use of politeness in Kadazandusun.